Implementation of Religious Moderation in Ketandan Village as The Adhesive and Unifier of The Nation - Maghfiroh, Ridaul; Fauziah, Arifah (Proceeding International Conference on Religion, Science and Education, 2024)
Moderation is an attitude that does not lean to the right or to the left, where people will be moderate and equal to differences. will act in the middle and equally towards differences. Moderate attitude in the context of in the context of religion is the choice to have a perspective, attitude, and behavior in the middle of the extremes, between the extremes. Ketandan Village is an area also known as Chinatown. This is where Ketandan village is the center of Chinese settlement during the Dutch era, which occupied Ketandan village since 250 years ago since 250 years ago. Every Lunar New Year the place celebrates by holding an event around the Ketandan village area. This event has been event has been running for about 15 years, in the performances are not only from the Chinese arts but also Islamic and Indonesian arts. Therefore, the researcher chose Ketandan Village as the object of research. Ketandan is the object of research. This article is written using descriptive qualitative This article is written using descriptive qualitative field research method, which is a research that is carried out based on the views, strategies, and implementation of the model. Based on the views, strategies, and implementation of the model by drawing the problem based on the findings, based on the findings. so that readers can understand and receive information that is clearly valid. So that readers can understand and receive information that is clear in its validity. The purpose of this writing is, among others, to know the history of Ketandan village and the attitude of the community in the scope of religious moderation.